1985
DOI: 10.1080/02652038509373535
|View full text |Cite
|
Sign up to set email alerts
|

Chromium in foods and the diet

Abstract: Food is the main source of chromium intake by man. Chromium is fairly evenly distributed throughout the various food groups examined, but highest concentrations of chromium are found in the meat, fish, fruit and sugar groups. Mean dietary chromium intakes in the UK (1976-78) were between 80 and 107 micrograms/day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Smart and Sherlock (1985) reported that while canned fruits contained significantly higher levels of chromium than fresh fruits, that it was not due to the tin can used for packaging. Instead, they proposed that the elevated levels were the result of extraction of chromium from the stainless steel cooking vats used during processing, due to the presence of malic and citric acids in fruits.…”
Section: Foods Which May Serve As a Significant Source Of Chromiummentioning
confidence: 96%
See 1 more Smart Citation
“…Smart and Sherlock (1985) reported that while canned fruits contained significantly higher levels of chromium than fresh fruits, that it was not due to the tin can used for packaging. Instead, they proposed that the elevated levels were the result of extraction of chromium from the stainless steel cooking vats used during processing, due to the presence of malic and citric acids in fruits.…”
Section: Foods Which May Serve As a Significant Source Of Chromiummentioning
confidence: 96%
“…The relatively high levels are most likely the result of fortification rather than being due to the levels in the grains since uptake of chromium by plants has been shown to be limited (Smart and Sherlock, 1985). Canned tomatoes, mushrooms, and pineapple also contained significant levels of chromium, again, most likely introduced during processing and packaging.…”
Section: Foods Which May Serve As a Significant Source Of Chromiummentioning
confidence: 98%
“…This fact, in accordance with the reviewed literature in the general adult population,', ' 1,17-19 9 shows the scarce quantitative relevance which, for essential metals, the non-alimentary exogenic contribution exert in our area. 12 I .. I Figure 1 Distribution of results.…”
Section: Analytical Proceduresmentioning
confidence: 96%
“…In this respect, attention must focused on the relationship between the human health and the metabolized trivalent chromium supplied in food. Safety of some seafoods (lobster, shrimp, prawn), for example, should be treated with caution, as they are particularly high in chromium content [6]. These authors suggested that mean dietary chromium intake by man ranged between 80 and 107 μg.day −1 .…”
mentioning
confidence: 98%